CMC and CNF-based intelligent pH-responsive color indicator films integrated with shikonin to monitor fish freshness. (August 2021) - Ezati, Parya; Priyadarshi, Ruchir; Bang, Yeong-Ju; Rhim, Jong-Whan
Abstract: Intelligent pH-responsive color indicator films based on carboxymethyl cellulose (CMC) and cellulose nanofibers (CNF) were prepared using shikonin extracted from Lithospermum erythrorhizon roots. The addition of shikonin did not affect the thermal stability and water vapor barrier properties of the film; however, the surface hydrophobicity increased significantly. The shikonin-added films showed high antioxidant activity, especially in aqueous solutions. The color indicator films showed a noticeable color response function for various pH values, showed reddish-pink at pH below 7, and turned reddish-purple, purple, and light blue as the pH increased from 7 to 12. When the indicator film was used to monitor the fish freshness, it showed a reddish-pink for fresh fish (pH = 5.7) and turned blue-violet after 36 h, indicating that it was spoiled (pH = 6.9). The shikonin-added color indicator films with a distinct discoloration function between a weak acid and weak alkali are likely to be applied to monitor seafood quality. Highlights: Shikonin extracted from Lithospermum erythrorhizon was introduced as active agent. Shikonin-incorporated carbohydrate-based food pH indicator films were developed. The films possessed high hydrophobic and antioxidant properties. The films displayed visible color response to basic pH solutions and ammonia vapor. The developed films were successfully applied to monitor packed fish freshness.